Precursors for liver gluconeogenesis in periparturient dairy cows* - M. Larsen (Animal, 2013)
The review is based on a compiled data set from studies quantifying liver release of glucose concomitant with uptake of amino acids (AA) and other glucogenic precursors in periparturient dairy cows. It has become dogma that AAs are significant contributors to liver gluconeogenesis in early lactation, presumably accounting for the observed lack of glucogenic precursors to balance estimated glucose need. Until recently, there has been paucity in quantitative data on liver nutrient metabolism in the periparturient period. Propionate is the quantitatively most important glucogenic precursor throughout the periparturient period. However, the immediate post partum increment in liver release of glucose is not followed by an equivalent increment in propionate uptake, because of the lower rate of increment in feed intake compared with the rate of increment in requirements for milk synthesis. The quantitative data on liver metabolism of AA do not support the hypothesis that the rapid post partum increase in net liver release of glucose is supported by increased utilisation of AA for gluconeogenesis. Only alanine is likely to contribute to liver release of glucose through its role in the inter-organ transfer of nitrogen from catabolised AA. AAs seem to be prioritised for anabolic purposes, indicating the relevance of investigating effects of supplying additional protein to post partum dairy cows. Combining data from quantitative and qualitative experimental techniques on L-lactate metabolism point to the conclusion that the quantitatively most important adaptation of metabolism to support the increased glucose demand in the immediate post partum period is endogenous recycling of glucogenic carbon through lactate. This is mediated by a dual site of adaptation of metabolism in the liver and in the peripheral tissues, where the liver affinity for L-lactate is increased and glucose metabolism in peripheral tissues is shifted towards L-lactate formation over complete oxidation.